Effect of Wheat Bran of Reduced Phytic Acid Content on the Quality of Batter and Sponge Cake. Issue 3 (11th December 2012) - Majzoobi, Mahsa; Pashangeh, Safoora; Farahnaky, Asgar
Abstract The main aim of this study was to include hydrothermaled and yeast fermented wheat bran (0%, 5%, 10%, 15% and 20%, w/w) in the sponge cake recipe to increase the application of the bran in human diet. The phytic acid content of the control reduced from 29.0 to 15.8 and 21.5 mg/g after hydrothermal and fermentation, respectively. The hydrothermaled barn had 9.5% fiber content that was higher than the control (8.5%) and fermented bran (8.8%). Addition of the hydrothermaled bran resulted in highest batter density and consistency, lowest cake volume, darkest color and hardest texture. Nevertheless, the organoleptic properties of the cakes were similar to the control when no more than 10% of all kinds of the bran were included. In total, inclusion of maximum 10% hydrothermaled bran into the sponge cake recipe resulted in an acceptable cake with lowest phytic acid content. Practical Applications Wheat bran is an undervalued byproduct of wheat milling factories that contains high level of dietary fiber and many other nutrients. Therefore, inclusion of wheat bran in human diet can enhance his general health. Nevertheless, the phytic acid content of the bran should be reduced before its application. The results of this study can be applicable for the cake or confectionary producers who want to incorporate wheat bran of reduced phytic acid content in the sponge cake recipe. Hydrothermal and fermentation treatments were applied to reduce the phytic acid content of the bran. These two treatments can be used by the wheat milling industry as a further treatment to reduce the phytic acid content of the bran to increase its nutrition value.